Enhancing the Development of Sustainable Modes of Transportation in Developing Countries: Challenges and Opportunities - Mohammed Dahim (Salehan Institute of Higher Education, 2021)
All modes of transport can be seen to bring some influence to bear on a country’s economic growth, health, and environment. However, the impact differs among developing countries. This paper presents an assessment and evaluation of the development of a sustainable transportation system in the Kingdom of Saudi Arabia (KSA). For this study, data were collected about the four transportation modes of sea, air, road and rail. The data were analyzed to determine the current condition, needs, challenges, and opportunities for improvement for each mode of transportation. Problems associated with each transportation mode were addressed and solutions to overcome these problems were recommended. The results indicate that while sea transportation provides the country with freight transport, it is of limited service to passengers in the Gulf region or on the Red Sea. Air transportation meets the needs of Saudi Arabia with international connections, but domestic flights provide limited passenger transport to the wealthy and are not an effective mode of transport for short distances. Road transport is the most popular mode for the general public but is associated with numerous problems such as the environment, health, noise, a high accident rate, and being the first cause of death in the country. Rail transportation seems to be the mode which is most sustainable for the future. It is essential that KSA meets public demand for public transportation with a reliable, cost effective, and safe public transportation system. Doi: 10.28991/cej-2021-03091776 Full Text: PDF